(untitled) (Comprehensive Journal of Science, 2026)
Socialization is considered the essential process that shapes an individual’s personality and adapts them to the norms of their society through the transmission of cultural heritage. Childhood is the cornerstone of societal progress, and it focuses on analyzing the variables that refine a child’s behavior and values. It highlights the family as the primary institution responsible for the moral continuity of society, as the nature of the relationship between parents directly affects the child’s psychological security and emotional balance. It also details the impact of parenting styles, warning against patterns of harshness, authoritarianism, indulgence, and inconsistency that lead to disorders such as anxiety and aggression, in contrast to the "normal approach" that produces an independent and creative personality. The educational level of the parents also acts as a guide to parenting styles. More educated parents tend to use dialogue and grant freedom rather than resorting to harshness. Economic status affects a family’s ability to meet the demands of development, as financial hardship can lead to family breakdown and disruption in child-rearing. Furthermore, a larger number of children can lead to a decline in individual attention and the emergence of authoritarian methods of maintaining order. Finally, the study highlights the growing role of media in socialization through the repetition of behavioral models, emphasizing the necessity of parental supervision to prevent children from acquiring consumerist values ​​or negative behaviors.